Tingkat Adopsi Teknologi Budidaya dan Fermentasi Biji Kakao oleh Petani dan Hubungannya dengan Sifat-Sifat Inovasi (Kasus Petani Kakao di Sungai Geringging Kabupaten Padang Pariaman) - Zulrasdi Zulrasdi (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2019)
The rapid development of the area of ​​cocoa plantations in West Sumatra is inseparable from the high desire of the community.a. This study aims to determine the level of adoption of cocoa bean cultivation and fermentation technology, see the relationship of relative benefits, relationship of level of suitability, relationship of complexity, relationship to ease of testing, and relationship between ease of observation and adoption of cocoa bean cultivation and fermentation technology innovations. The study was conducted from September to November 2016 in Sungai Geringging District, Padang Pariaman Regency. Sampling was carried out with proportional simple random sampling.. Primary data collection is done by questionnaire or questionnaire. Data collected are Characteristics of respondents, level of adoption of cocoa bean cultivation and fermentation technology innovations, relationship of relative benefits, relationship of degree of conformity, relationship of complexity level, relationship of ease of testing, and relationship of ease of observation with the adoption of seed cultivation and fermentation technology innovations cocoa. Data were analyzed descriptively and statistically by Spearman's rank correlation test. The results showed that the nature of innovation properties that have a significant relationship with the adoption of cocoa bean cultivation and fermentation technology innovation are the degree of conformity with the correlation value of 0.212 which has a low positive correlation, and the level of ease with a correlation value of 0.258, positively low correlation.